Faktor-Faktor Yang Berhubungan Dengan Penggunaan Masker Dalam Upaya Pencegahan Penyebaran Covid-19 Pada Siswa SD N 09 Bidar Alam Kecamatan Sangir Jujuan Kabupaten Solok Selatan - Muslimah, Ulfa Mifta; wel, Dar; Adriyanti, Sri Lestari; din, Awalud; Gusti, Awalia (Jurnal Kesehatan Lingkungan Mandiri, 2022)
This research is motivated by problems at SD N 09 Bidar Alam, it is still found that students use masks that do not match the correct technique which causes students to be susceptible to contracting COVID-19. to the students of SD N 09 Bidar Alam, Sangir Jujuan District, South Solok Regency. This type of research is quantitative with a cross-sectional research design, the population and sample of this study are students of SD N 09 Bidar Alam. Data collection techniques using a questionnaire. Processing and analyzing data with chi-square statistical test. The results of the study 72.2% of respondents chose to wear surgical masks, 63.6% of respondents did not use masks with the correct technique, 54.5% of respondents had good knowledge about the use of masks, 51.5% of respondents had negative attitudes towards the practice of using masks, 60.6% of respondents have less information about the correct use of masks. Statistics show a significant relationship between knowledge, attitudes, and health information with the use of masks with the correct technique with a p-value <0.05. It was concluded that knowledge, attitude, and health information were factors related to the use of masks with the correct technique. It is hoped that the school will carry out health campaigns or promotions directly or indirectly related to the use of masks with the correct technique.